A base de conhecimento TPACK na formação continuada do tutor dos cursos de licenciatura em educação a distância da UEMA: um estudo de caso - LIMA, Danielle Martins Leite Fernandes (2020)
Research on the initial and continued education of distance tutors from licentiate courses in distance learning modality at the State University of Maranhão (UEMA), to understand their conceptions of knowledge regarding Technological Pedagogical and Content Knowledge (TPACK) and their perspectives about what they need to know for the tutoring practice. It aims to know the academic and professional profiles of tutors and if they participate in continuing educational processes throughout their careers (lifelong learning), besides identifying what knowledge these tutors demonstrate, which ones need improvement and how this knowledge is applied in their practice. It is a study with qualitative and quantitative methodology, case study type, to guarantee the deepness necessary to the study and the case intersection in its context. To this end, three types of techniques where used in the research development: 1. Questionnaire applied with Google Docs to profile the tutors; 2. Interview with tutors who work in licentiate courses in distance modality at UEMA; 3. Discussion group in the Virtual Learning Environment (VLE). Data collected were categorized and the content was analyzed, keeping a dialogue with the theoretical framework that guides the study, as well as the objectives determined for this investigation. It discusses and relates the input, the technique, and the theoretical framework to create a general idea towards the research sample. Concerning the analysis, it is categorized as a case study since it describes the situation of the context where the investigation was conducted based on the initial research hypotheses. By using methodological triangulation, it aims to validate the quality of the results obtained, contributing to get the corroboration in the analysis of the analyzed phenomena. It approaches the concept of TPACK as the fundamental category that guided the research steps, aiming at observing if the tutors used the technologies pedagogically to apply the content of their specific areas, as well as the adoption of the knowledge basis TPACK and tutors' knowledge in licentiate courses in distance learning at UEMA. It discusses the concepts of Information Age based on a dialogue with Lévy (2009), Castells (2011), the concepts of Distance Learning according to Gonzalez (2005), Belloni (2015; 2001), Kenski (2013; 2010), Aretio (2002), Peters (2011), besides the concepts of Teaching Knowledge Basis and Teaching Knowledge found on Shulman (2005), Zeichner (1998; 2008), Mishra e Koeler (2006). It reinforces that tutors still ignore the concept and uses of TPACK in their teaching practices, which led us to reflect on the possibilities of offering continued education to tutors at the State University of Maranhão. It points out that towards the results obtained throughout the research, it is original research about the professors’ education for distance learning and the teaching and learning processes of tutors in the context of UEMA.